2016
DOI: 10.1021/acs.biochem.6b00610
|View full text |Cite
|
Sign up to set email alerts
|

Six-Transmembrane Epithelial Antigen of Prostate 1 (STEAP1) Has a Single b Heme and Is Capable of Reducing Metal Ion Complexes and Oxygen

Abstract: STEAP1, six-transmembrane epithelial antigen of prostate member 1, is strongly expressed in several types of cancer cells, particularly in prostate cancer, and inhibition of its expression reduces the rate of tumor cell proliferation. However, the physiological function of STEAP1 remains unknown. Here for the first time, we purified a mammalian (rabbit) STEAP1 at a milligram level, permitting its high-quality biochemical and biophysical characterizations. We found that STEAP1 likely assembles as a homotrimer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 34 publications
4
61
0
Order By: Relevance
“…S3D), which is missing in STEAP1. In line with this, STEAP3 and 4 exhibit a low micromolar affinity for FAD (Kd = ~1 µM) (26,29), whereas the affinity of STEAP1 for FAD is much weaker (Kd = 34 µM) (30). The cryo-EM density in this region could therefore correspond to a loosely bound FAD cofactor, although the weak density does not allow for modelling the complete cofactor.…”
Section: Architecturementioning
confidence: 94%
See 4 more Smart Citations
“…S3D), which is missing in STEAP1. In line with this, STEAP3 and 4 exhibit a low micromolar affinity for FAD (Kd = ~1 µM) (26,29), whereas the affinity of STEAP1 for FAD is much weaker (Kd = 34 µM) (30). The cryo-EM density in this region could therefore correspond to a loosely bound FAD cofactor, although the weak density does not allow for modelling the complete cofactor.…”
Section: Architecturementioning
confidence: 94%
“…A previous pioneering study reported the biophysical and electrochemical characterization of N-terminally truncated rabbit STEAP1, purified from insect cells in lauryl maltose neopentyl glycol (LMNG) detergent (30). Our initial attempts to purify full-length, human STEAP1 from mammalian HEK-cells using a similar protocol were hampered by the loss of the noncovalently bound heme-b cofactor during the purification, suggesting that STEAP1 was not natively folded.…”
Section: Biochemical Characterization Of Steap1mentioning
confidence: 99%
See 3 more Smart Citations